Evaluation of Beclin1 Effect on Apoptosis in Mouse Infected with Street Rabies Virus - Prizad, Homeira; Fazeli, Maryam; Mahmoudi, Minoo; Jananni, Alireza; Sheikholeslami, Farzaneh (Novelty in Biomedicine, 2020)
Background: Apoptosis is a programmed cell death in which certain cellular components are packed into small membrane vacuoles by immune cells. Different strains of rabies virus (RABV) have their own biological features, but their effects on apoptosis have been little known. The aim of current research was to evaluate Beclin 1 effect on apoptosis in the mouse infected with the street rabies virus. Materials and Methods: Exogenous Beclin1 overexpressed by the pIRES2-EGFP-Beclin1 vector in the cortex of NMRI mice. To evaluate the apoptosis, TUNEL assay was done on brain tissues of the rabid mice. Results: TUNEL assay data showed that small apoptotic cells were seen in the four groups that received the vector alone or with the SRABV, but no significant changes were observed. There are no signs of apoptosis in mouse normal brain cells. Conclusion: It was previously proven that overexpression of exogenous Beclin1 could induce autophagy but this study showed that overexpression of Beclin 1 does not cause apoptosis in rabies-infected cells.